The Cost of Coastal Zone Degradation in Georgia : A Tool for the Coastal Zone Adaptation and the Nationally Determined Contributions - World Bank (World Bank, Washington, DC, 2021)
The cost of environmental degradation (COED) report focuses on Georgia’s coastal zone. Georgia’s coastal zone is crucial to the national economy but has been affected by substantial environmental degradation. This report estimates the impact of degradation that occurred in 2017, as a result of pollution, flooding, coastal erosion, and agricultural soil and forest degradation in eight of coastal Georgia’s municipalities. Economic values are expressed in 2017 prices. This study is a first attempt to estimate the COED of Georgia’s coastal zone and so features some uncertainties regarding data and information used for cost estimates. Therefore, estimates of this report provide an order of magnitude of the COED for selected areas affected by degradation. Raising awareness of the magnitude of coastal degradation is a critical step towards enacting positive change. Therefore, this report focuses on coastal Georgia’s eight municipalities, estimating, in monetary terms, the COED in 2017. Estimates provide an indication of the real magnitude of damage and of the urgency of action needed to protect Georgia’s coastal zone. The report is organized as follows: chapter one gives introduction. Chapter two provides an overview of the methods used for estimating the COED and covers the report limitations. Chapter three reports estimate of costs related to pollution, chapter four addresses the cost of flooding and coastal erosion, while chapter five analyzes costs associated with soil and forest degradation. Chapter six qualifies potential risks due to climate change in the coastal zone of Georgia. Chapter seven outlines some recommendations that Georgia may take to reduce annual degradation costs.